The Brand Name's Role in the Purchase Decisions at the Beginning of the Xxist Century. Empirical Evidences from the North-Eastern Part of Romania - Laura Diaconu (CES Working Papers, 2012)
Considering the great impact of consumers' behavior on the economic activity, in the present paper we intend to identify and analyze the way in which the purchase decisions of the individuals are influenced or not by the products' brand name, taking the particular case of the Romanian consumers' behavior. The exploratory research was conducted using two methods. An analysis of the secondary data offered by the specialized literature was followed by a primary data collection through a structured survey, conducted on 335 people form the North-Easternpart of Romania. The results indicate that most of the respondents are mainly influenced, in their purchase decisions, by the quality of the products and price-quality ratio, the brand being situated only on the third or fourth place. However, the majority of the consumers are buying durable branded goods and, in the case of the non-durable products, they opt for both types (branded or with private label).
Keywords: D12; 330; brand name; consumers' loyalty; price; quality Romania